2014
DOI: 10.1080/13546805.2013.877385
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive correlates of psychosis in patients with Parkinson's disease

Abstract: Although hypothetical, our data may suggest that the hippocampus is a neural substrate underlying the occurrence of psychosis, sleep disturbance and cognitive impairment in PD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 101 publications
2
7
0
Order By: Relevance
“…Greater memory deficits have also been found for black-and-white visual stimuli than for coloured visual stimuli, perhaps reflecting more-limited encoding of visually impoverished stimuli in patients with visual hallucinations 47 . A transitive inference test thought to measure hippocampal function has uncovered impairments in patients with PD psychosis 48 .…”
Section: Mechanisms and Risk Factorsmentioning
confidence: 99%
“…Greater memory deficits have also been found for black-and-white visual stimuli than for coloured visual stimuli, perhaps reflecting more-limited encoding of visually impoverished stimuli in patients with visual hallucinations 47 . A transitive inference test thought to measure hippocampal function has uncovered impairments in patients with PD psychosis 48 .…”
Section: Mechanisms and Risk Factorsmentioning
confidence: 99%
“…The loss of dopaminergic (DA) neurons is responsible for the development of PD motor symptoms (Liu, 2006 ). DA therapies, such as L-DOPA and dopamine agonists, either have a short half-life or may induce psychiatric side effects (Olanow et al, 2004 ; Moustafa et al, 2014 ). These issues raise the urgent need for an alternative form of therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep disorders occur in three quarters of autopsy-confirmed cases of dementia with Lewy bodies, but may not necessarily correlate with sleep satisfaction; in addition to attentional, executive functioning, and visuospatial impairments, the presence of impaired verbal learning helps identify prodromal dementia with Lewy bodies in patients with sleep disorders 41 . Moreover, it has been shown that the severity of psychotic symptoms in patients with Parkinson's disease is directly associated with the severity of cognitive impairment and sleep disturbances 42 .…”
Section: Discussionmentioning
confidence: 99%